2020
DOI: 10.1038/s41598-020-78623-5
|View full text |Cite
|
Sign up to set email alerts
|

Microchemical analysis of Leonardo da Vinci’s lead white paints reveals knowledge and control over pigment scattering properties

Abstract: Leonardo da Vinci (1452–1519) is a key artistic and scientific figure of the Renaissance. He is renowned for his science of art, taking advantage of his acute observations of nature to achieve striking pictorial results. This study describes the analysis of an exceptional sample from one of Leonardo’s final masterpieces: The Virgin and Child with St. Anne (Musée du Louvre, Paris, France). The sample was analyzed at the microscale by synchrotron-based hyperspectral photoluminescence imaging and high-angular X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…Different ratios of these compounds and different crystallite sizes can be associated with different post-synthesis treatments of the white powder obtained after lead corrosion following the traditional production of lead white [ 7 ]. This information was used to explain the presence of different lead whites in Leonardo da Vinci’s Virgin and Child with St. Anne [ 8 ]. Determining precisely the pigment composition is also very important for conservation purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Different ratios of these compounds and different crystallite sizes can be associated with different post-synthesis treatments of the white powder obtained after lead corrosion following the traditional production of lead white [ 7 ]. This information was used to explain the presence of different lead whites in Leonardo da Vinci’s Virgin and Child with St. Anne [ 8 ]. Determining precisely the pigment composition is also very important for conservation purposes.…”
Section: Introductionmentioning
confidence: 99%
“…In certain cases, such as the Virgin and Child with St. Anne (c. 1503–1519, Musée du Louvre), he used a preparatory buildup composed of a gesso (a mixture of water-soluble glue with gypsum, CaSO 4 ·2H 2 O) ground layer, typical in the Italian Renaissance, followed by a priming layer containing lead white (LW, a mixture of two lead carbonates, cerussite, PbCO 3 , denoted as “Cer” and hydrocerussite, Pb 3 (CO 3 ) 2 (OH) 2 , denoted as “HCer”) . In other paintings such as the La Belle Ferronnière (c. 1495–1497, Musée du Louvre), he applied an orange oil-based ground layer, made of white and red lead (Pb 3 O 4 ) directly on the wooden panel.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true for the ground layer(s), i.e., the thick layer(s) applied between the wooden panel and the paint layers as extensively described by Ravaud et al 2 In certain cases, such as the Virgin and Child with St. Anne (c. 1503−1519, Museé du Louvre), he used a preparatory buildup composed of a gesso (a mixture of water-soluble glue with gypsum, CaSO 4 •2H 2 O) ground layer, typical in the Italian Renaissance, followed by a priming layer containing lead white (LW, a mixture of two lead carbonates, cerussite, PbCO 3 , denoted as "Cer" and hydrocerussite, Pb 3 (CO 3 ) 2 (OH) 2 , denoted as "HCer"). 3 In other paintings such as the La Belle Ferronniere (c. 1495−1497, Museé du Louvre), he applied an orange oil-based ground layer, made of white and red lead (Pb 3 O 4 ) directly on the wooden panel. A hypothesis proposed by Ravaud et al to explain these different ground layers is related to the size of the different wooden panels: 2 a large panel like the one used for the St. Anne would have been difficult for Leonardo to build by himself and might have thus been ordered in a carpenter studio where the wooden support was frequently also covered by gesso (or gypsum) as was common in Italy.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In general, elemental, chemical speciation, and crystalline phase maps can be obtained by raster scanning the sample over 2D regions. Less frequently, SR X-ray analyses are combined with other SR-based techniques, such as micro-photoluminescence ( μ PL) or micro-Fourier Transform Infrared ( μ FTIR) spectroscopy (Salvadó et al, 2011, 2014; Lluveras-Tenorio et al, 2012; Pouyet et al, 2015; Langlois et al, 2017; Gonzalez et al, 2020 b ). Such non-X-ray techniques provide complementary information on the molecular composition, offering a unique integrated approach for the analysis of painting materials.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, SR μ PL proved to be a powerful tool for characterizing complex cultural heritage materials down to the submicrometric scale, thanks to the sensitivity of PL to small variations of local environment (Thoury et al, 2016; Hageraats et al, 2019; Thoury et al, 2019). For example, recently SR μ PL studies on lead white paint have demonstrated that the spectral unfolding of the PL emission can be used to perform semi-quantitative characterization of the spatial distribution of different lead white crystalline phases in paint layers, without exposing samples to a high dose of ionizing radiation, as could be the case when using synchrotron X-ray beams (Gonzalez et al, 2020 b ). A major limitation of PL remains the difficulty in interpreting the luminescence spectrum and associating the emission with a specific compound.…”
Section: Introductionmentioning
confidence: 99%